Feeding distribution and behaviour of Shelduck in relation to food supply - Bryant, D M; Leng, J (Wildfowl, 1975)
The pattern of Shelduck Tadorna tadorna feeding was studied at Skinflats on the Firth of Forth, during the winter of 1972-1973. An association between the intensity of feeding and the distribution and abundance of the main food, Hydrobia ulvae, was observed. This association was influenced by tidal movements and weather conditions and possibly by human disturbance. The behaviour of Hydrobia in relation to water depth apparently strongly influenced both the spatial distribution of feeding flocks and the feeding method used.